Academic Senate Minutes 2020-02-27 - Academic Senate:::::::::
Agenda Approved. Minutes of 4/22/2021 Approved. Special Student Report. Chair Report. Information item: Credit Hour Policy. Provost Report. President Report. Reconsideration of AFS/PDS Statement on the Teaching of Sensitive Materials – endorsement not approved. From EPC: Name change for Electrical and Computer Engineering –Second Reading - Approved. Vice Chair Report. Vice President for Student Affairs Report. From APARC: Program Review Policy revision – Second Reading – Approved. Resolution in Support of AAPI Community and Related Curriculum – Second Reading – Approved. Associated Students Report. Statewide Senators Report. CFA Report. SAC Report. FSAC Report. APARC Report.